2019
DOI: 10.1371/journal.pone.0216156
|View full text |Cite
|
Sign up to set email alerts
|

Playground lead levels in rubber, soil, sand, and mulch surfaces in Boston

Abstract: Rubber surfacing is often used in playgrounds due to its potential injury prevention benefits and as a way to recycle waste tires. Available research on chemicals in recycled rubber has focused on synthetic turf applications, but is limited for playground rubber surfacing. Potential lead contamination from vulcanizing agents used in rubber surfacing are a possible concern; however this has not been researched. We examined levels of lead in poured-in-place rubber and compared them to levels in soil, sand, and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…A more useful approach for evaluating potential human exposures is to assess the weathering-dependent metal surface release (MSR) from TCR materials, particularly those having long environmental durability, such as children’s playground tiles. Such studies have been rarely found in the literature thus far, and relevant data are therefore very limited if ever existed 29 .…”
Section: Introductionmentioning
confidence: 99%
“…A more useful approach for evaluating potential human exposures is to assess the weathering-dependent metal surface release (MSR) from TCR materials, particularly those having long environmental durability, such as children’s playground tiles. Such studies have been rarely found in the literature thus far, and relevant data are therefore very limited if ever existed 29 .…”
Section: Introductionmentioning
confidence: 99%
“…First, particles formed due to the wear of tires, and their amount can vary between 5% and 30%. 36 The second way is from the recycled rubber which is used as the construction material for the artificial reef, [37][38][39] as fill material for playgrounds, 40,41 as highway embankments, 42 and as embankment fill material. 43,44 Nowadays rubber is more and more used as the construction material, for artificial lawns and similar, and since it consist of polycyclic aromatic hydrocarbons (PAH) and heavy metals, it is harmful Figure 1.…”
Section: Introductionmentioning
confidence: 99%